A method for preparing SiC-Al2O3 composite coating on metal surface

The preparation of SiC-Al2O3 composite coating on metal nozzles by electrophoretic deposition and precursor conversion method solves the problem of insufficient coating uniformity and oxidation resistance in the prior art, and achieves efficient and uniform coating preparation and extended nozzle service life.

CN119020782BActive Publication Date: 2025-04-18CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411104074.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-04-18
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The prior art is difficult to prepare SiC-Al2O3 composite ceramic coatings with excellent thermal erosion resistance on metal nozzles, especially to ensure the uniformity of the coating and oxidation resistance on nozzles of complex structures.

Method used

The aluminum oxide coating was prepared on the metal surface by electrophoretic deposition method, and the polycarbosilane was converted into a silicon carbide coating by precursor conversion method, combining nano-alumina powder and nano-silicon carbide as inert fillers to ensure the uniformity and mechanical properties of the coating.

Benefits of technology

The SiC-Al2O3 composite coating is efficiently prepared on complex structure metal nozzles, which significantly improves the oxidation resistance and mechanical properties of the coating and extends the service life of the nozzle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119020782B_ABST
    Figure CN119020782B_ABST
Patent Text Reader

Abstract

The invention discloses a metal surface SiC-Al 2 O 3 A method for preparing a composite coating, wherein an aluminum oxide coating is deposited on a metal surface by electrophoresis and then sintered to obtain an aluminum-containing 2 O 3 The metal of the coating; the Al-containing 2 O 3 The metal of the coating is immersed in a solution containing polycarbosilane to obtain a solution containing precursor and Al 2 O 3 The present invention can prepare SiC-Al on the metal surface. 2 O 3 The composite coating and the two-step liquid phase method are applicable to various workpieces with complex structures. The preparation method of the invention is simple, the raw materials are readily available, the price is cheap, no special equipment is required, and it is easy to be mass-produced industrially.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a SiC-Al2O3 composite coating on a metal surface, in particular to a method for preparing the SiC-Al2O3 composite coating on a metal surface by adopting electrophoretic deposition and precursor conversion methods. Background Art

[0002] The nozzle is one of the key components in the water-coal slurry burner. To solve the problem of short service life of metal nozzles, there are currently two common solutions: one is to replace metal with cemented carbide materials with higher hardness and higher elastic modulus or ceramic materials with better wear resistance and corrosion resistance, but their machinability is poor and the production cost is high; the other is to prepare a protective coating with excellent thermal erosion resistance on the metal nozzle to increase the service life of the water-coal slurry nozzle.

[0003] At present, many people at home and abroad have prepared protective coatings on coal-water slurry nozzles, but most of them are cemented carbide coatings. The preparation of cemented carbide coatings on metal nozzles effectively improves their service life, but its protective effect is still insufficient, and its service life is still lower than that of coal-water slurry nozzles made of cemented carbide and ceramic materials. Ceramic coal-water slurry nozzles have the longest service life. At present, the research on coal-water slurry ceramic nozzles focuses on their structure and materials, while there is little research on ceramic coatings.

[0004] SiC ceramics have the advantages of high hardness, high strength, good toughness (relative to other ceramic materials), high temperature resistance, thermal shock resistance, corrosion resistance, erosion resistance, wear resistance, light weight and good thermal conductivity. Single SiC ceramics still cannot meet the requirements of water-coal slurry nozzles working at high temperatures for a long time, while Al2O3 has good oxidation resistance and high temperature stability, and can form a mullite structure with SiC. The combination of alumina and silicon carbide can obtain SiC-Al2O3 composite ceramics with significantly improved mechanical properties and high temperature resistance, which can meet the requirements of water-coal slurry nozzles working for a long time in harsh environments.

[0005] Currently, the preparation methods of ceramic coatings can be divided into four categories: vapor deposition, high-energy spraying, laser cladding and liquid phase method. However, this single process is difficult to meet the requirements of preparing ceramic coatings on nozzles with complex structures and ensure the anti-oxidation properties of the coatings. Summary of the invention

[0006] In order to solve the problems of the prior art, the present invention provides a method for preparing a SiC-Al2O3 composite coating on a metal surface. The method first prepares an aluminum oxide coating by electrophoretic deposition and then prepares a silicon carbide coating by combining a precursor conversion method. The method is suitable for various metal nozzles with complex structures. At the same time, the use of a special deposition liquid can ensure the uniformity and integrity of the coating, thereby ensuring the anti-oxidation performance and mechanical properties of the coating.

[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing a SiC-Al2O3 composite coating on a metal surface. The method comprises the following steps: electrophoretically depositing an aluminum oxide coating on the metal surface, and then sintering the coating to obtain a metal containing the Al2O3 coating; immersing the metal containing the Al2O3 coating in a solution containing polycarbosilane to obtain a metal containing a precursor and an Al2O3 composite coating, and then subjecting the metal to high-temperature cracking to obtain the metal; the deposition liquid used for the electrophoretic deposition comprises aluminum sol, nano-alumina powder and anhydrous ethanol.

[0008] The key to the technical solution of the present invention is to first use electrophoretic deposition to provide a large driving force to uniformly deposit the gel-like aluminum hydroxide in the deposition liquid onto the metal surface, and then convert it into an Al2O3 coating through sintering; at the same time, the polymer material polycarbosilane with good fluidity and processability is wrapped in a precursor conversion method, and finally the polycarbosilane is converted into a silicon carbide coating through high-temperature pyrolysis.

[0009] The aluminum sol in the deposition solution used in the electrophoretic deposition of the present invention is a gel-like aluminum hydroxide, and it also contains anhydrous ethanol solvent. Since the hydroxyl hydrogen atoms of ethanol are very active and weakly acidic, and the aluminum sol particles also contain hydroxyl groups that are easy to form hydrogen bonds, they will absorb the partially ionized H + , which causes the aluminum sol particles to carry a positive charge. During the electrophoretic deposition process, some of the sol particles will undergo electrophoretic migration and deposit at the negative electrode. + The electrons at the negative electrode generate hydrogen, and the electrophoretic deposition process is also accompanied by the electrolysis of water. Both of these situations will have an adverse effect on the deposition, causing the uniformity and firmness of the coating to deteriorate. Therefore, in the subsequent drying process, the sol shrinks and the gel network structure shrinks, causing the coating to crack. The inventors have found that adding inert filler nano-alumina powder to the deposition liquid and co-depositing it on the negative electrode with the sol particles can effectively avoid the cracking of the coating caused by the shrinkage of the sol. This is because the addition of the inert filler nano-alumina powder can be evenly dispersed in the coating to play an anchoring role, hindering the shrinkage movement of the sol particles.

[0010] The inventors have found that the aluminum oxide powder used is of nanometer level and has better dispersibility in the deposition liquid, which is more conducive to the aluminum oxide particles being wrapped by the sol particles and deposited on the negative electrode together. If the particle size of the aluminum oxide powder is too large, the aluminum oxide will be deposited at the bottom and cracking of the coating cannot be effectively avoided.

[0011] As a preferred solution, the metal is tungsten or stainless steel, and before electrophoretic deposition, it is first polished step by step with silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone in sequence.

[0012] As a preferred solution, the stainless steel material is selected from at least one of 302 stainless steel, 304 stainless steel, 304L stainless steel, 316 stainless steel, 316L stainless steel and 321 stainless steel.

[0013] As a preferred solution, the deposition liquid is prepared by mixing aluminum sol with anhydrous ethanol, adding nano-alumina powder under stirring, and then magnetically stirring for 10 to 30 minutes and ultrasonically oscillating for 10 to 30 minutes.

[0014] As a preferred solution, the volume percentage of aluminum sol and anhydrous ethanol is (30-60)%:(40-70)%, and 1-6g of nano-alumina powder is added to every 100mL of the mixed solution of aluminum sol and anhydrous ethanol.

[0015] The concentration of aluminum sol and the amount of nano-alumina powder added in the present invention have a direct impact on the deposition effect. When the concentration of aluminum sol is too small, fewer sol particles may not be evenly deposited on the substrate, resulting in discontinuity and uneven thickness of the coating; when the concentration of aluminum sol is too large, the overly thick coating will shrink during the drying process after electrophoretic deposition, causing cracking of the coating. It is further preferred that the volume percentage of aluminum sol and anhydrous ethanol is (35-45)%: (55-65)%. The addition of an appropriate amount of nano-alumina powder can increase the deposition amount and effectively avoid cracking of the coating caused by sol shrinkage. However, too much nano-alumina powder will cause the deposition liquid to become viscous, which is not conducive to the electrophoretic deposition of sol particles. At the same time, if the viscosity of the deposition liquid is too large, when the sample is extracted from the deposition liquid, part of the deposition liquid will adhere to the coating, resulting in poor uniformity of the coating. It is further preferred that 3-4g of nano-alumina powder is added to every 100mL of the mixed solution of aluminum sol and anhydrous ethanol.

[0016] As a preferred solution, the preparation process of the aluminum sol is: under constant temperature and stirring conditions, aluminum sec-butoxide and nitric acid are slowly added to water in sequence, mixed for 1 to 4 hours, and then ultrasonically dispersed for 10 to 40 minutes.

[0017] As a preferred solution, the molar ratio of water, aluminum sec-butoxide and nitric acid is (60-90): (1-20): (0.1-5). In the present invention, aluminum sec-butoxide is added to excess water and the pH value is adjusted with nitric acid to generate aluminum hydroxide sol particle precipitation. The present invention uses aluminum sec-butoxide to prepare aluminum sol, which belongs to the hydrolysis method. The size and stability of the sol particles can be adjusted by controlling the pH value and temperature. The advantage of the hydrolysis method is that it is easy to operate, relatively low in cost, and suitable for large-scale production.

[0018] As a preferred solution, the conditions of the electrophoretic deposition are: metal as the negative electrode, graphite as the positive electrode, the deposition voltage is 3 to 10V, and the deposition time is 3 to 10min. The magnitude of the deposition voltage determines the strength of the constant voltage electric field in the deposition liquid, which in turn affects the driving force exerted on the charged particles. Therefore, the deposition voltage has a great influence on the deposition current and deposition rate. When the deposition voltage is very small, the driving force of the constant voltage electric field in the deposition liquid on the charged particles is not enough to cause the charged particles to migrate and deposit on the electrode. When the deposition voltage is too large, the electrolysis of water will be aggravated, and the number of bubbles on the electrode plate will increase, resulting in poor uniformity and firmness of the coating. At the same time, excessive deposition voltage will also bring about excessive deposition current and deposition rate, which is prone to excessive thickness or even cracking of the coating.

[0019] As a preferred scheme, the sintering conditions are: heating to 100-200°C at 1-5°C / min in an argon atmosphere, keeping warm for 1-3 hours, then directly heating to 600-1400°C at 2-5°C / min or heating to 600-1400°C in stages, keeping warm for 1-3 hours, and finally cooling to 620-900°C at a cooling rate of 2-10°C / min and then cooling to room temperature with the furnace.

[0020] As a preferred solution, the solution also includes xylene and nano-silicon carbide. After obtaining the aluminum oxide coating, the present invention grinds the polycarbosilane into powder and dissolves it in xylene with continuous stirring, and at the same time adds a small amount of nano-silicon carbide as an inert filler until it is completely dissolved, and then immerses the prepared metal containing the aluminum oxide coating therein, and then slowly pulls it, and repeats the immersion and pulling process multiple times. Some gas products will be produced during the high-temperature cracking process of polycarbosilane, and their escape will have a certain effect on the pore structure and densification of the silicon carbide coating, and by adding a certain amount of nano-silicon carbide, the volume shrinkage during the pyrolysis conversion of the precursor can be suppressed and compensated.

[0021] As a preferred solution, the mass percentage of the polycarbosilane and xylene is (10-40)%:(60-90)%.

[0022] As a preferred solution, the amount of the nano-silicon carbide added accounts for 5% to 15% of the total mass of the solution.

[0023] As a preferred scheme, the conditions for high-temperature cracking are: in a tubular furnace, directly heating to 1000-1400°C at a heating rate of 2-10°C / min under an argon environment and keeping warm for 1-4h or heating to 1000-1400°C in stages, and then directly cooling to 500-600°C at a cooling rate of 2-10°C / min or cooling to 500-600°C in stages and then cooling to room temperature with the furnace.

[0024] Principles and advantages

[0025] The present invention firstly adds aluminum sec-butoxide to excess deionized water through a colloidal gel method, and adjusts the pH value with nitric acid to generate sol particle precipitation, thereby preparing an aluminum sol, which is mainly composed of gel-like aluminum hydroxide. Then, electrophoretic deposition is used to replace the traditional deposition method, and the two processes are organically combined. The deposition of particles in the sol-gel method relying solely on capillary action and adhesion is avoided. Electrophoretic deposition provides a greater driving force for deposition, accelerates the deposition rate, and also improves the shortcomings of the coating that is not dense enough that is easy to occur during ordinary electrophoretic deposition. However, the coating after electrophoretic deposition is still aluminum hydroxide, which needs to be converted into an aluminum oxide coating after high-temperature sintering.

[0026] The precursor conversion method utilizes the good fluidity, formability, processability and structural designability of polymer materials to obtain inorganic ceramic materials by high-temperature cracking of organic polymer precursors. In the present invention, polycarbosilane is dissolved in xylene and a small amount of nano-silicon carbide is added as an inert filler, and then the polycarbosilane is wrapped by multiple dipping and pulling. Finally, the polycarbosilane is cracked by high-temperature sintering to generate a silicon carbide ceramic coating. At the same time, since γ-Al2O3 is irreversibly converted into α-Al2O3 in the range of 1050 to 1500°C, the inner layer of the alumina coating will be completely converted into α-Al2O3 during the final high-temperature sintering.

[0027] The electrophoretic deposition and precursor conversion methods in the present invention are both liquid-phase coating preparation methods, which have no requirements on the shape of the substrate and can be applied to prepare coatings on various metal components with complex structures. At the same time, the requirements on equipment and preparation costs are low, and they are suitable for large-scale industrial production.

[0028] The method for preparing SiC-Al2O3 composite coating on metal surface by liquid phase method provided by the present invention has the following beneficial effects:

[0029] 1) The present invention adopts a two-step liquid phase method to prepare a SiC-Al2O3 composite coating on a metal surface, which is suitable for various metal components with complex structures and has good bonding with the substrate.

[0030] 2) The present invention can prepare a coating on the surface of metal tungsten or stainless steel by controlling the parameters of electrophoretic deposition and the temperature during the final sintering. At the same time, the electrophoretic deposition time and voltage can also be changed to obtain coatings of different thicknesses. The process is simple and highly controllable.

[0031] 3) The preparation method of the present invention is simple, the raw materials are readily available and cheap, no special equipment is required, and it is easy to carry out large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The present invention discloses a process flow for preparing SiC-Al2O3 composite coating on metal surface by liquid phase method.

[0033] Figure 2 This is a backscattered electron micrograph of the SiC-Al2O3 composite coating on the surface of 304 stainless steel.

[0034] Figure 3 This is the effect of different amounts of nano-alumina powder added on the deposition amount.

[0035] Figure 4 The effect of different deposition voltages on the deposition amount.

[0036] Figure 5 This is a comparison diagram of the aluminum oxide coatings prepared in Example 1 and Comparative Example 1 after drying. DETAILED DESCRIPTION

[0037] Example 1

[0038] This embodiment provides a method for preparing a SiC-Al2O3 composite coating on a metal surface by a liquid phase method, comprising the following steps:

[0039] 1. Preprocessing

[0040] The tungsten sheet (bare sample 1) was polished on 120#, 240#, 400#, and 600# silicon carbide sandpapers step by step, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.

[0041] 2. Preparation of deposition solution

[0042] Under the condition of water bath temperature of 85℃ and magnetic stirring, ASB (aluminum sec-butoxide) was slowly added to deionized water. After magnetic stirring, HNO3 was added (the molar ratio of deionized water, aluminum sec-butoxide, and HNO3 was: deionized water: aluminum sec-butoxide: HNO3 = 90:1:0.2 molar ratio). Then magnetic stirring was performed for 2h, and ultrasonic dispersion was performed for 30min to obtain a stable aluminum sol. Subsequently, 40mL of anhydrous ethanol was added to 60mL of aluminum sol, and 3g of nano-alumina powder was added under continuous stirring. After magnetic stirring for 30min, ultrasonic vibration was performed for 30min.

[0043] 3. Electrophoretic deposition

[0044] Immerse the sanded tungsten sheet and graphite sheet in the deposition solution, with the tungsten sheet as the negative electrode and the graphite sheet as the positive electrode. Deposit for 3 minutes at 4V. After drying, put it into a tubular furnace, evacuate it at room temperature, and then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Raise the temperature to 120℃ at 1℃ / min, keep it warm for 3h, then raise the temperature to 1000℃ at 3℃ / min, then raise the temperature to 1300℃ at 2℃ / min, keep it warm for 2h, and finally cool it to 900℃ at a cooling rate of 2℃ / min, then cool it to room temperature with the furnace to obtain an aluminum oxide coating.

[0045] 4. Dipping and pulling

[0046] 50g of polycarbosilane was ground into powder and dissolved in 100mL of xylene with constant stirring. At the same time, 15g of nano-silicon carbide (the amount added was 15% of the total mass of the solution) was added as an inert filler until it was completely dissolved. Then, the metal tungsten with an aluminum oxide coating was immersed in it, and then slowly pulled up, and the immersion and pulling process was repeated three times. The ratio of xylene to polycarbosilane was composed of 40% polycarbosilane and 60% xylene by mass percentage.

[0047] 5. Precursor transformation

[0048] Dissolve polycarbosilane in xylene, then immerse the tungsten sheet with alumina coating in it, slowly pull it, and repeat the immersion and pulling three times. After drying at room temperature, place it in a tube furnace, evacuate it at room temperature, then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Then increase the temperature to 1000℃ at a heating rate of 3℃ / min and keep it for 2h, then increase the temperature to 1300℃ at a heating rate of 2℃ / min and keep it for 2h, finally cool it down to 1000℃ at a cooling rate of 2℃ / min, then cool it down to 600℃ at a cooling rate of 5℃ / min and cool it to room temperature with the furnace to obtain SiC-Al2O3 composite coating.

[0049] The comparison of the anti-oxidation performance of the SiC-Al2O3 composite coating prepared in Example 1 and metal tungsten is shown in Table 2. It can be seen from Table 2 that the surface of the SiC-Al2O3 composite coating in Example 1 has no discoloration, indicating that its anti-oxidation performance is greatly improved.

[0050] Example 2

[0051] This embodiment provides a method for preparing a SiC-Al2O3 composite coating on a stainless steel surface by a liquid phase method, comprising the following steps:

[0052] 1. Preprocessing

[0053] The 304 stainless steel sheet was polished step by step on 120#, 240#, 400#, and 600# silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.

[0054] 2. Preparation of deposition solution

[0055] Under the condition of water bath temperature of 85℃ and magnetic stirring, ASB (aluminum sec-butoxide) was slowly added to deionized water. After magnetic stirring, HNO3 was added (the molar ratio of deionized water, aluminum sec-butoxide, and HNO3 was: deionized water: aluminum sec-butoxide: HNO3 = 90:1:0.2 molar ratio). Then magnetic stirring was performed for 2h, and ultrasonic dispersion was performed for 30min to obtain a stable aluminum sol. Subsequently, 40mL of anhydrous ethanol was added to 60mL of aluminum sol, and 3g of nano-alumina powder was added under continuous stirring. After magnetic stirring for 30min, ultrasonic vibration was performed for 30min.

[0056] 3. Electrophoretic deposition

[0057] Immerse the stainless steel sheet and graphite sheet polished with sandpaper in the deposition liquid, with the stainless steel sheet as the negative electrode and the graphite sheet as the positive electrode. Deposit for 3 minutes at 3V. After drying, put it into a tube furnace, evacuate it at room temperature, and then fill the furnace chamber with argon gas to atmospheric pressure and ensure that argon gas flows in the furnace chamber during use. Raise the temperature to 120℃ at 1℃ / min, keep it warm for 3h, then raise the temperature to 620℃ at 3℃ / min, keep it warm for 3h, and finally cool it to room temperature with the furnace to obtain an aluminum oxide coating.

[0058] 4. Dipping and pulling

[0059] 50g of polycarbosilane was ground into powder and dissolved in 100mL of xylene with constant stirring. 15g of nano-silicon carbide was added as an inert filler until it was completely dissolved. Then the metal tungsten with alumina coating was immersed in it and slowly pulled up. The immersion and pulling process was repeated three times. The ratio of xylene to polycarbosilane was 40% by mass and 60% by mass.

[0060] 5. Precursor transformation

[0061] Dissolve polycarbosilane in xylene, then immerse the stainless steel sheet with alumina coating in it, slowly pull it, and repeat the immersion and pulling three times. After drying at room temperature, place it in a tubular furnace, evacuate it at room temperature, and then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Then increase the temperature to 900℃ at a heating rate of 3℃ / min and keep it for 2h, then increase the temperature to 1200℃ at a heating rate of 1℃ / min and keep it for 2h, finally cool it down to 1000℃ at a cooling rate of 2℃ / min, then cool it down to 600℃ at a cooling rate of 5℃ / min and cool it to room temperature with the furnace to obtain SiC-Al2O3 composite coating.

[0062] The comparison of the oxidation resistance of the SiC-Al2O3 composite coating prepared in Example 2 and the 304 stainless steel sheet is shown in Table 1. It can be seen from Table 1 that the oxidation resistance of the SiC-Al2O3 composite coating in Example 2 is greatly improved.

[0063] Example 3

[0064] This embodiment provides a method for preparing a SiC-Al2O3 composite coating on a metal surface by a liquid phase method, comprising the following steps:

[0065] 1. Preprocessing

[0066] The tungsten sheet (bare sample 2) was polished on 120#, 240#, 400#, and 600# silicon carbide sandpapers, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 min, and then dried;

[0067] 2. Preparation of deposition solution

[0068] Under the condition of water bath temperature of 85℃ and magnetic stirring, ASB (aluminum sec-butoxide) was slowly added to deionized water. After magnetic stirring, HNO3 was added (the molar ratio of deionized water, aluminum sec-butoxide, and HNO3 was: deionized water: aluminum sec-butoxide: HNO3 = 90:1:0.2 molar ratio). Then magnetic stirring was performed for 2h, and ultrasonic dispersion was performed for 30min to obtain a stable aluminum sol. Subsequently, 40mL of anhydrous ethanol was added to 60mL of aluminum sol, and 3g of nano-alumina powder was added under continuous stirring. After magnetic stirring for 30min, ultrasonic vibration was performed for 30min.

[0069] 3. Electrophoretic deposition

[0070] Immerse the sanded tungsten sheet and graphite sheet in the deposition solution, with the tungsten sheet as the negative electrode and the graphite sheet as the positive electrode. Deposit for 4 minutes at 3V. After drying, put it into a tubular furnace, evacuate it at room temperature, and then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Raise the temperature to 120℃ at 1℃ / min, keep it warm for 3h, then raise the temperature to 1000℃ at 3℃ / min, then raise the temperature to 1300℃ at 2℃ / min, keep it warm for 2h, and finally cool it to 800℃ at a cooling rate of 2℃ / min, then cool it to room temperature with the furnace to obtain an aluminum oxide coating.

[0071] 4. Dipping and pulling

[0072] 50g of polycarbosilane was ground into powder and dissolved in 100mL of xylene with constant stirring. At the same time, 10g of nano-silicon carbide (the amount added was 10% of the total mass of the solution) was added as an inert filler until it was completely dissolved. Then, the metal tungsten with an aluminum oxide coating was immersed in it, and then slowly pulled up, and the immersion and pulling process was repeated three times. The ratio of xylene to polycarbosilane was composed of 40% polycarbosilane and 60% xylene by mass percentage.

[0073] 5. Precursor transformation

[0074] Dissolve polycarbosilane in xylene, then immerse the tungsten sheet with alumina coating in it, slowly pull it, and repeat the immersion and pulling three times. After drying at room temperature, place it in a tube furnace, evacuate it at room temperature, then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Then increase the temperature to 1000℃ at a heating rate of 3℃ / min and keep it for 2h, then increase the temperature to 1300℃ at a heating rate of 2℃ / min and keep it for 2h, finally cool it down to 1000℃ at a cooling rate of 2℃ / min, then cool it down to 600℃ at a cooling rate of 5℃ / min and cool it to room temperature with the furnace to obtain SiC-Al2O3 composite coating.

[0075] The comparison of the oxidation resistance of the SiC-Al2O3 composite coating prepared in Example 3 and metal tungsten is shown in Table 2. It can be seen from Table 2 that the oxidation resistance of the SiC-Al2O3 composite coating in Example 3 is greatly improved.

[0076] Example 4

[0077] This embodiment provides a method for preparing a SiC-Al2O3 composite coating on a metal surface by a liquid phase method, comprising the following steps:

[0078] 1. Preprocessing

[0079] The 316 stainless steel sheet was polished on 120#, 240#, 400#, and 600# silicon carbide sandpaper step by step, and then ultrasonically cleaned with anhydrous ethanol and acetone for 15 minutes and blown dry.

[0080] 2. Preparation of deposition solution

[0081] Under the condition of water bath temperature of 85℃ and magnetic stirring, ASB (aluminum sec-butoxide) was slowly added to deionized water. After magnetic stirring, HNO3 was added (the molar ratio of deionized water, aluminum sec-butoxide, and HNO3 was: deionized water: aluminum sec-butoxide: HNO3 = 90:1:0.2 molar ratio). Then magnetic stirring was performed for 2h, and ultrasonic dispersion was performed for 30min to obtain a stable aluminum sol. Subsequently, 40mL of anhydrous ethanol was added to 60mL of aluminum sol, and 3g of nano-alumina powder was added under continuous stirring. After magnetic stirring for 30min, ultrasonic vibration was performed for 30min.

[0082] 3. Electrophoretic deposition

[0083] Immerse the stainless steel sheet and graphite sheet polished with sandpaper in the deposition liquid, with the stainless steel sheet as the negative electrode and the graphite sheet as the positive electrode. Deposit for 3 minutes at 3V. After drying, put it into a tube furnace, evacuate it at room temperature, and then fill the furnace chamber with argon gas to atmospheric pressure and ensure that argon gas flows in the furnace chamber during use. Raise the temperature to 120℃ at 1℃ / min, keep it warm for 3h, then raise the temperature to 620℃ at 3℃ / min, keep it warm for 3h, and finally cool it to room temperature with the furnace to obtain an aluminum oxide coating.

[0084] 4. Dipping and pulling

[0085] 50g of polycarbosilane was ground into powder and dissolved in 100mL of xylene with constant stirring. At the same time, 10g of nano-silicon carbide (the amount added was 10% of the total mass of the solution) was added as an inert filler until it was completely dissolved. Then, the metal tungsten with an aluminum oxide coating was immersed in it, and then slowly pulled up, and the immersion and pulling process was repeated three times. The ratio of xylene to polycarbosilane was composed of 40% polycarbosilane and 60% xylene by mass percentage.

[0086] 5. Precursor transformation

[0087] Dissolve polycarbosilane in xylene, then immerse the stainless steel sheet with alumina coating in it, slowly pull it, and repeat the immersion and pulling three times. After drying at room temperature, place it in a tubular furnace, evacuate it at room temperature, and then fill the furnace chamber with argon to atmospheric pressure and ensure that argon flows in the furnace chamber during use. Then increase the temperature to 900℃ at a heating rate of 3℃ / min and keep it for 2h, then increase the temperature to 1200℃ at a heating rate of 1℃ / min and keep it for 2h, finally cool it down to 1000℃ at a cooling rate of 2℃ / min, then cool it down to 600℃ at a cooling rate of 5℃ / min and cool it to room temperature with the furnace to obtain SiC-Al2O3 composite coating.

[0088] The comparison of the oxidation resistance of the SiC-Al2O3 composite coating prepared in Example 4 and the 316 stainless steel sheet is shown in Table 1. It can be seen from Table 1 that the oxidation resistance of the SiC-Al2O3 composite coating in Example 4 is greatly improved.

[0089] Example 5

[0090] Under the conditions of deposition voltage of 5V and deposition time of 5min, the effect of the addition amount of nano-alumina powder in the range of 5-45g / L (0.5-4.5g of nano-alumina powder was added to every 100mL of the mixed solution of aluminum sol and anhydrous ethanol) on the deposition amount was investigated. The other conditions were the same as those in Example 1. The results are shown in FIG. Figure 3 shown.

[0091] The results show that when the content of nano-alumina powder in the electrophoretic deposition solution is greater than 10g / L (1g of nano-alumina powder is added to every 100mL of the mixed solution of aluminum sol and anhydrous ethanol), the coating deposition amount increases significantly, and the coating cracking caused by the shrinkage of the sol is also alleviated. When the content of nano-alumina powder in the electrophoretic deposition solution is greater than 30g / L, the effect of the increase in the content of nano-alumina powder on the coating deposition amount begins to decrease. Moreover, with the continuous addition of nano-alumina powder, the viscosity of the deposition solution also increases. Therefore, the content of nano-alumina powder in the electrophoretic deposition solution is most suitable when it is 30g / L.

[0092] Example 6

[0093] When the volume percentage of aluminum sol and anhydrous ethanol in the deposition solution is 40%:60%, the amount of nano-alumina powder added is 30g / L, and the deposition time is 5min, the effect of the deposition voltage of 3-15V on the deposition amount is investigated. The remaining steps and conditions are the same as in Example 1. The results are as follows: Figure 4 shown.

[0094] The results show that when other process conditions remain unchanged, the deposition amount increases with the increase of deposition voltage. However, when the deposition voltage exceeds 11V, this trend begins to slow down. This is because when the deposition voltage exceeds 11V and the deposition time is 5min, the deposition and scouring of particles on the negative electrode basically reach a balance. When the deposition voltage is less than 11V and the deposition time is 5min, the deposition rate of particles on the negative electrode is greater than the scouring rate, and the deposition amount continues to increase with time. However, when the deposition voltage exceeds 7V, the prepared coating is prone to cracking due to sol shrinkage during the drying process.

[0095] Comparative Example 1

[0096] The only difference compared with Example 1 is that no nano alumina powder is added to the deposition liquid, and the remaining steps and conditions are the same to obtain an alumina coating.

[0097] The aluminum oxide coating of Comparative Example 1 is as follows Figure 5 (b), and Figure 5 (a) Compared with the case without adding nano-alumina powder, the dried alumina coating has obvious cracking.

[0098] Comparative Example 2

[0099] The only difference from Example 1 is that nano-silicon carbide is not added during the impregnation and pulling process, and the other steps and conditions are the same.

[0100] The results show that the coating cracks and falls off after pyrolysis, with only a small amount of silicon carbide attached to the alumina coating.

[0101] The invention can prepare SiC-Al2O3 composite coating on metal tungsten or stainless steel, and the two-step liquid phase method is applicable to various workpieces with complex structures. The preparation method of the invention is simple, the raw materials are easily available, the price is cheap, no special equipment is required, and it is easy to be mass-produced industrially.

[0102] Table 1 shows the mass changes of the original 304 stainless steel, 316 stainless steel and the coatings of Example 2 and Example 4 after oxidation for 20 hours.

[0103] Table 1

[0104]

[0105] Table 2 shows the mass changes of the original metal tungsten and the coatings of Example 1 and Example 3 after oxidation for 10 hours.

[0106] Table 2

[0107]

[0108] The embodiments of the present invention are described above, but the present invention is not limited to the above embodiments. Various changes can be made according to the purpose of the invention. Any changes, modifications, substitutions, combinations or simplifications made according to the spirit and principle of the technical solution of the present invention should be equivalent replacement methods. As long as they meet the purpose of the invention and do not deviate from the technical principles and inventive concepts of the present invention, they belong to the protection scope of the present invention.

Claims

1. A method for preparing a SiC-Al2O3 composite coating on a metal surface, characterized in that: After depositing an aluminum oxide coating on a metal surface by electrophoresis, sintering the metal to obtain a metal containing an Al2O3 coating; immersing the metal containing the Al2O3 coating in a solution containing polycarbosilane to obtain a metal containing a precursor and an Al2O3 composite coating, and then pyrolyzing the metal at high temperature to obtain; The deposition liquid used in the electrophoretic deposition includes aluminum sol, nano-aluminum oxide powder and anhydrous ethanol; The deposition liquid is prepared by mixing aluminum sol with anhydrous ethanol, adding nano-alumina powder under stirring, magnetically stirring for 10 to 30 minutes and ultrasonically vibrating for 10 to 30 minutes; The volume percentage of aluminum sol and anhydrous ethanol is (30-60)%: (40-70)%, and 1-6 g of nano-alumina powder is added to every 100 mL of the mixed solution of aluminum sol and anhydrous ethanol; The preparation process of the aluminum sol is as follows: under the condition of constant temperature and stirring, aluminum sec-butoxide and nitric acid are slowly added to water in sequence, mixed for 1 to 4 hours, and then ultrasonically dispersed for 10 to 40 minutes; The polycarbosilane-containing solution also includes xylene and nano-silicon carbide; The mass percentage of the polycarbosilane and xylene is (10-40)%: (60-90)%; The amount of the nano-silicon carbide added is 5% to 15% of the total mass of the solution containing polycarbosilane.

2. The method for preparing a SiC-Al2O3 composite coating on a metal surface according to claim 1, characterized in that: The metal is tungsten or stainless steel, and before electrophoretic deposition, it is first polished step by step with silicon carbide sandpaper, and then ultrasonically cleaned with anhydrous ethanol and acetone in sequence.

3. The method for preparing a SiC-Al2O3 composite coating on a metal surface according to claim 1, characterized in that: The molar ratio of water, aluminum sec-butoxide and nitric acid is (60-90): (1-20): (0.1-5).

4. The method for preparing a SiC-Al2O3 composite coating on a metal surface according to any one of claims 1 to 3, characterized in that: The conditions of the electrophoretic deposition are: metal as the negative electrode, graphite as the positive electrode, the deposition voltage is 3-10V, and the deposition time is 3-10min.

5. The method for preparing a SiC-Al2O3 composite coating on a metal surface according to claim 4, characterized in that: The sintering conditions are as follows: heating to 100-200°C at 1-5°C / min in an argon atmosphere, keeping the temperature for 1-3h, then heating to 600-1400°C, keeping the temperature for 1-3h, and finally cooling to 620-900°C at a cooling rate of 2-10°C / min and then cooling to room temperature with the furnace.

6. The method for preparing a SiC-Al2O3 composite coating on a metal surface according to claim 1, characterized in that: The conditions for high temperature cracking are: in a tubular furnace, first heating to 1000-1400° C. in an argon environment and keeping the temperature for 1-4 hours, then cooling to 500-600° C. and then cooling to room temperature along with the furnace.

Citation Information

Patent Citations

  • Method for preparing SiC / Al2O3 coating by using precursor conversion method

    CN103898499A